Canopy and soil thermal patterns to support management of irrigated vineyards - Costa, J.M. (2022)
Irrigated viticulture expanded fast in Southern European countries such as Portugal to optimize berry yield and quality and to increase vine’s longevity. However, intensive irrigation increases pressure over the local and regional water resources, that are getting scarcer, and increases also management costs. Additionally, row crops such as grapevine, are more vulnerable to heat stress due to the additional effects of soil heat fluxes which can negatively influence canopy and berry thermal condition. Therefore, a better understanding of grapevine responses (diurnal and seasonal) to environmental factors (air temperature, soil water) and agronomic practices (deficit irrigation, soil management) are on demand by the industry. Ground based thermography was used to monitor the vertical profile of canopy temperature as well as soil temperature patterns along the day and season as means to assess plant water status and predict risks of heat stress damage. As part of the EU-INNOVINE project, field trials were carried in 2013, 2014 and 2015 in Alentejo (South Portugal). We examined the diurnal and seasonal response of two V. vinifera varieties Aragonez (syn. Tempranillo) and Touriga Nacional subjected to sustained deficit irrigation (SDI), and regulated deficit irrigation (RDI, about 50% of the SDI). Diurnal canopy (TC), and soil surface (Tsoil) temperatures were assessed by thermography. Punctual measurements of leaf temperature with thermal couples, leaf water potential and leaf gas exchange were also done. TC values were above the optimal temperature for leaf photosynthesis during part of the day light period (11:00-14:00h to 17:00h), especially under stressful atmospheric conditions (high VPD, high Tair) and under regulated deficit irrigation. Tsoil was on average about 10-15°C higher than TC. We found strong correlation between TC (derived from thermography) and major physiological traits (leaf water potential and leaf gas exchange). Our results suggest that Tc can be explored as a simple but robust non-intrusive thermal indicator of grapevine performance and also as a parameter to feed grapevine growth models and to estimate heat and water fluxes in irrigated vineyards